The Application of Abolition to Corruption Offenses and Disruption of the Integrated Criminal Justice System - Wahyu Zulzaman; Ali Masyhar (The Indonesian Journal of International Clinical Legal Education, 2026)
An integrated criminal justice system requires consistency, coordination, and synchronization among its subsystems to achieve the objectives of criminal sanctioning. As corruption is recognized as an extraordinary crime, it necessitates firm, consistent, and coordinated legal responses throughout every stage of the criminal justice process. Against this backdrop, the granting of presidential abolition in the corruption case involving Thomas Trikasih Lembong at the prosecution stage raises fundamental questions regarding its compatibility with the principles of an integrated criminal justice system. This study examines two main issues: the implementation of integrated criminal justice system principles within Indonesia’s anti-corruption policy framework and the consistency of granting abolition in the Thomas Trikasih Lembong case with those principles. Employing a normative legal research method, this study utilizes statutory, conceptual, and case approaches. The findings indicate that the granting of abolition disrupted structural, substantive, and cultural synchronization within the criminal justice system, thereby affecting the continuity of legal proceedings and weakening the consistency of anti-corruption policy. The study further highlights the need for clearer normative limitations on the exercise of presidential abolition powers to ensure alignment with the objectives of criminal law enforcement and to preserve the integrity of Indonesia’s anti-corruption efforts. In addition, the issue offers valuable insights for clinical legal education, particularly in fostering students’ capacity to undertake systemic and critical analyses of legal policies within the broader framework of criminal justice governance.